Creativity-Contingent Rewards, Intrinsic Motivation, and Creativity: The Importance of Fair Reward Evaluation Procedures - Saether, Erik Andreas (Frontiers in Psychology, 2020)
Pay for performance is a common practice used by organizations to increase employees’ motivation and performance, and creativity-contingent rewards have been shown to support creativity, but are all creativity-contingent rewards equal? Procedural justice can potentially affect the way that creativity-contingent rewards impact employees’ intrinsic motivation and creativity. To shed light on this practice-relevant issue, this study investigates how aspects of procedural justice – reward allocation clarity and reward evaluation fairness – impact changes in intrinsic motivation and creativity in the presence of creativity-contingent rewards. Using an incomplete factorial pretest-posttest between subjects design with four reward conditions and one control (no reward) condition, I analyzed changes in intrinsic motivation and creativity. Relative to the control condition, significant increases in both intrinsic motivation and creativity were found in the reward conditions with high evaluation fairness. However, reward allocation clarity did not yield any significant effects on changes in intrinsic motivation and creativity. The results highlight the importance of fair evaluation procedures for determining rewards if creativity-contingent rewards are to increase intrinsic motivation and creativity.